AGE DISTRIBUTION OF CARIES LESIONS IN CHILDREN'S PERMANENT TEETH - A BASIS FOR THE CHOICE OF A THERAPEUTIC SOLUTION - Milena Peneva; Maya Rashkova; Liliya Doychinova (Peytchinski Publishing, 2007)
The object of the study is administered to the child the correlation between the reversible and irreversible caries lesions must be ascertained. A 1000 children aged 6-15, divided into 10 groups each comprising a hundred children, were subjected to epidemiological research. Childhood and adolescence is characterised by an active and progressing caries process. The process is evinced in a big number of caries lesions at different stages of development. Many of the lesions are reversible nevertheless. The irreversible lesions are few in number, especially in the youngest patients. As the children grow older, the number of lesions increases, including the number fo irreversible lesions. This is indicative of the fact that no management of caries process has been administered, which makes it possible for the process to progress freely. The big share of reversible pathology makes it pretty obvious what should the character of medical treatment be. Reversible lesions can be cured non-operatively and preventively. Such a treatment requires systematic control of the caries process and a remineralisation non-operative treatment of the lesion. In this way full regeneration of the structure affected can be achieved which is the only adequate therapeutic approach.